LONGITUDINAL STRUCTURAL CHANGES IN LATE-ONSET RETINAL DEGENERATION. Issue 12 (December 2016) - Cukras, Catherine; Flamendorf, Jason; Wong, Wai T.; Ayyagari, Radha; Cunningham, Denise; Sieving, Paul A.
Abstract : Purpose: To characterize longitudinal structural changes in early stages of late-onset retinal degeneration to investigate pathogenic mechanisms. Methods: Two affected siblings, both with a S163R missense mutation in the causative gene C1QTNF5, were followed for 8+ years. Color fundus photos, fundus autofluorescence images, near-infrared reflectance fundus images, and spectral domain optical coherence tomography scans were acquired during follow-up. Results: Both patients, aged 45 and 50 years, had good visual acuities (>20/20) in the context of prolonged dark adaptation. Baseline color fundus photography demonstrated yellow–white, punctate lesions in the temporal macula that correlated with a reticular pattern on fundus autofluorescence and near-infrared reflectance imaging. Baseline spectral domain optical coherence tomography imaging revealed subretinal deposits that resemble reticular pseudodrusen described in age-related macular degeneration. During follow-up, these affected areas developed confluent thickening of the retinal pigment epithelial layer and disruption of the ellipsoid zone of photoreceptors before progressing to overt retinal pigment epithelium and outer retinal atrophy. Conclusion: Structural changes in early stages of late-onset retinal degeneration, revealed by multimodal imaging, resemble those of reticular pseudodrusen observed in age-related macular degeneration and other retinal diseases. Longitudinal follow-up of these lesions helps elucidate their progression to frank atrophy and may lend insight into the pathogenic mechanisms underlying diverse retinal degenerations. Abstract : Multimodal imaging in early stages of late-onset retinal degeneration reveals findings of reticular pseudodrusen that initially occurs in the setting of preserved ellipsoid zones, and over time progresses to areas of retinal pigment epithelium thickening and detachment with ellipsoid zones disruption, and then eventually to overt retinal pigment epithelium and outer retinal atrophy.